Transcultural translation of the Minnesota Handwriting Assessment for the Brazilian context - Pasculli, Adriane Guzman [UNESP]; Hiraga, Cynthia Yukiko [UNESP]; Pellegrini, Ana Maria [UNESP] (Cuba Editora, 2017)
Introduction: Handwriting is a complex human hand skill and its assessment is one of the several challenges encountered by teachers in the literacy process. Objective: The present study aimed to validate and adapt transculturally, for the Brazilian context, the Minnesota Handwriting Assessment (MHA), an instrument developed by Judith Reisman. Method: A total of 448 children enrolled in the 2nd and 3rd school years from the public school system and two school teachers who served as examiners, participated in the present study. The validation method utilized was the Cross-Cultural Adaptation and it was applied for the validation of the D'Nealian style. Results: First, it was verified the equivalence of concepts, semantics and idiom resulting from translation and retranslation of the MHA to Portuguese language. Then, teachers were asked to use the adapted MHA instrument. The Intraclass Correlation Coefficient (ICC) for the test-retest reliability was 0.92 for legibility, 0.90 for form, 0.99 for alignment and 0.89 for spacing, being significant in all categories. About the inter-rater reliability, the ICC was 0.89 for legibility, 0.99 for alignment, 0.98 for size, and 0.90 for spacing, reaching level of significance in these categories. The ICC 0.53 for form category did not reach level of significance which could be related to variability of the handwriting pattern of the Brazilian children. Conclusion: The cross-cultural adaptation for the Portuguese language and the satisfactory results obtained from the validation of the D'Nealian print style for the handwriting assessment allows its use in the Brazilian System of Education with restriction to the category of form.
Keywords: Handwriting; Cross-Cultural Adaptation; Validation